An Extension of a Theorem of Hamada on the Cauchy Problem with Singular Data - Lamport, Leslie (American Mathematical Society, 1973)
At the time, and perhaps still today, a math student "copyrighted" his (seldom her) thesis results by announcing them in a short note in the Bulletin of the AMS. Normally, a complete paper would be published later. But I never did that, since I left math for computer science after completing my thesis.